2008
DOI: 10.1021/jm070880t
|View full text |Cite
|
Sign up to set email alerts
|

Rationalizing the Activities of Diverse Cholecystokinin 2 Receptor Antagonists Using Molecular Field Points

Abstract: Cholecystokinin 2 receptor antagonists encompass a wide range of structures. This makes them unsuitable candidates for existing 3D-QSAR methods and has led us to develop an alternative approach to account for their observed biological activities. A diverse set of 21 antagonists was subjected to a novel molecular field-based similarity analysis. The hypothesis is that compounds with similar field patterns will bind at the same target site regardless of their underlying structure. This initial report demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Without knowledge about a receptor structure, it is possible to find a limited number of alignments for chemically diverse compounds in certain conformations in which molecular fields and/or volumes are very similar. If all of these compounds have high affinity for the same receptor, it can be assumed that they participate in the alignment in their bioactive conformations and are "seen" identically by the receptor (Low and Vinter, 2008). Thus, such an alignment (i.e., template) is considered a model for the unknown active site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without knowledge about a receptor structure, it is possible to find a limited number of alignments for chemically diverse compounds in certain conformations in which molecular fields and/or volumes are very similar. If all of these compounds have high affinity for the same receptor, it can be assumed that they participate in the alignment in their bioactive conformations and are "seen" identically by the receptor (Low and Vinter, 2008). Thus, such an alignment (i.e., template) is considered a model for the unknown active site.…”
Section: Discussionmentioning
confidence: 99%
“…We used a ligand-based approach to molecular modeling that uses the field point approach developed by Cheeseright et al (2006Cheeseright et al ( , 2007 (see Materials and Methods). This approach allowed us to compare diverse molecules in terms of their field similarity (Cheeseright et al, 2006) and create an alignment of their bioactive conformations as "seen" by the receptor (Low and Vinter, 2008). This alignment or template provides an accurate pharmacophore model of an unknown active site (Cheeseright et al, 2006(Cheeseright et al, , 2007Low and Vinter, 2008).…”
Section: Characterization Of Novel Fpr1/fpr2 Agonists 165mentioning
confidence: 99%
“…52,53 Cresset software employs extrema in ligand fields as guides in ligand alignment. 54 Schrodinger package offers PHASE as its 3D QSAR capability. 55 Two approaches that use a complementary biological target field to refine ligand-based 3D QSAR models are COMBINE 56 and AFMoC 57 programs; two other pioneering 3D QSAR methodologies, HASSLE 58 and MSTD 59 also deserve mentioning.…”
Section: History and Evolution Of Qsarmentioning
confidence: 99%
“…Because most of the reported small-molecule natural inhibitors of f MLF-induced functional responses were not evaluated in competition binding assays, we used molecular modeling to predict how well these compounds fit the FPR1 antagonist pharmacophore and their potential for binding to FPR1. The FPR1 antagonists described so far represent a wide range of chemotypes, and it is consequently difficult to derive meaningful SAR on structural grounds [206]. Recently, we built a pharmacophore model of FPR1 antagonists [79] based on field point methodology developed by Cheeseright et al .…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%
“…[207, 208]. This approach allowed us to compare diverse molecules in terms of their electrostatic field similarity and create an alignment of their bioactive conformations [206]. We found that three potent small-molecule synthetic non-peptide FPR1 antagonists that were identified previously using high-throughput screening and/or lead optimization [6-ethyl-2-methyl-3-(1-methyl-1 H -benzimidazol-2-yl)-4-oxo-4 H -chromen-7-yl acetate, N -(1 S )(1-(benzoimidazol-2-yl)-3-(methylthio)propyl)-5-ethoxy-3-methylbenzofuran-2-carboxamide, and 6-benzyl-3-(2-chlorophenyl)-5-methyl-2-(trifluoromethyl)pyrazolo[1,5-a]pyrimidin-7(1 H )-one (designated previously by us as compounds 1 , 5 , and 7 )] [78, 209] could be overlaid simultaneously with good correspondence of their molecular fields to form an FPR1 antagonist pharmacophore template [79].…”
Section: Small-molecule Non-peptide Fpr1 Antagonists and Their Synmentioning
confidence: 99%